Possibility of identifying plant components of the diet of Harpalus rufipes (Coleoptera, Carabidae) by visual evaluation - D. Y. Reshetniak; O. Y. Pakhomov; V. V. Brygadyrenko (Regulatory Mechanisms in Biosystems, 2017)
Harpalus rufipes (De Geer, 1774) is a trans-palearctic, polyzonal, habitat generalist species, which is usually the most numerous ground beetle species in agricultural ecosystems and forest plantations. In laboratory conditions, 50 H. rufipes imagoes were placed in separate containers, each individual being fed over several days with seeds of a single species of plant, the total number of plant species being ten. Then the content of the beetles’ intestine were analyzed using Lugol’s iodine stain for visualizing starch granules. Native agents of ground seeds of plants and also of seeds treated by a fermentative agent from a mammalian pancreas were used for control. Granules of starch from seeds of Triticum aestivum L., Hordeum vulgare L. and Secale cereale L. were only insignificantly broken down by enzymes in the intestines of H. rufipes. The starch granules of Avena sativa L., Panicum miliaceum L., Sorghum drummondii (Steud.) Millsp. and Chase, Fagopyrum esculentum Moench and Sinapis arvensis L. were also insignificantly affected in the beetles’ intestine compared to the agent affected by enzymes of vertebrate animals. Starch granules of Beta vulgaris L. seeds affected by the enzymes became deformed and fragmented. Sometimes only their fragments remained. Seeds with a high content of fats such as seeds of Juglans regia L. were digested poorly in the intestine of H. rufipes (drops of fat could be seen surrounding certain food particles, which obstructed their digestion). The results of microscopic study of the intestinal content of mixed phytophage ground beetles of agricultural environments will help in identifying mechanisms of regulation of trophic chains by polyphage species, and will help advance the study of gregarine infection rates among ground beetles.